The hippocampus supports multiple cognitive processes through relational binding and comparison - Olsen, Rosanna K.; Moses, Sandra N.; Riggs, Lily; Ryan, Jennifer D. (Frontiers in Human Neuroscience, 2012)
It has been well established that the hippocampus plays a pivotal role in explicit long-term recognition memory. However, findings from amnesia, lesion and recording studies with non-human animals, eye-movement recording studies, and functional neuroimaging have recently converged upon a similar message: the functional reach of the hippocampus extends far beyond explicit recognition memory. Damage to the hippocampus affects performance on a number of cognitive tasks including recognition memory after short and long delays and visual discrimination. Additionally, with the advent of neuroimaging techniques that have fine spatial and temporal resolution, findings have emerged that show the elicitation of hippocampal responses within the first few hundred milliseconds of stimulus/task onset. These responses occur for novel and previously viewed information during a time when perceptual processing is traditionally thought to occur, and long before overt recognition responses are made. We propose that the hippocampus is obligatorily involved in the binding of disparate elements across both space and time, and in the comparison of such relational memory representations. Furthermore, the hippocampus supports relational binding and comparison with or without conscious awareness for the relational representations that are formed, retrieved and/or compared. It is by virtue of these basic binding and comparison functions that the reach of the hippocampus extends beyond long-term recognition memory and underlies task performance in multiple cognitive domains.